PROFIL TINGKAT BERPIKIR KREATIF SISWA KELAS VII SMP NEGERI 16 SURAKARTA DALAM PEMECAHAN MASALAH ARITMATIKA SOSIAL DITINJAU DARI MOTIVASI DAN GENDER - Linda Sunarya; Tri Atmojo Kusmayadi; Gatut Iswahyudi (Jurnal Pembelajaran Matematika, 2013)
Abstract. This study aimed to describe: (1) the creative thinking level of male Junior High School students, who had high motivation in solving some problems in appropriate to Polya’s Steps, (2) the creative thinking level of female Junior High School students, who had high motivation in solving some problems in appropriate to Polya’s steps, (3) the creative thinking level of male Junior High School students, who had medium motivation in solving some problems in appropriate to Polya’s steps, (4) the creative thinking level of female Junior High School students, who had medium motivation in solving some problems in appropriate to Polya’s steps, (5) the creative thinking level of male Junior High School students, who had low motivation in solving some problems in appropriate to Polya’s steps, (6) the creative thinking level of female Junior High School students, who had low motivation in solving some problems in appropriate to Polya’s steps. This study was a qualitative study. The subject of this study was 7th grade students of Public Junior High School 16 Surakarta. The subject selection procedure of this study was purposive sampling. The subject used in this study were six subjects of study that was a male student with high motivation, a female student with high motivation, a male student with medium motivation, a female student with medium motivation, a male student with low motivation, and a female student with low motivation. The instrument in collecting data was classification of students’ learning motivation, problem solving assignment sheet, and interview manual. Based on the study had been carried out, there was one student, who was belonged to the creative thinking abilities level 4, one student was belonged to the creative thinking abilities level 2, and four student was belonged to the creative thinking abilities level 0. In the creative thinking abilities level 4, the student was able to demonstrate fluency, flexibility, and novelty. In the creative thinking abilities level 2, the student was able to demonstrate novelty, but not able to demonstrate any fluency and flexibility. In the creative thinking abilities level 0, the student was not able to demonstrate the fluency, flexibility, or novelty. Keywords: Creative thinking level, Problem solving, Motivation, Gender